Design and Development of Audio Data Transmission Using Visible Light Communication - Budi Waluyo, Catur; Benedictus Mardwianta; Oswald Richfild Tambunan; Lasmadi (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2020)
Technological developments have opened up a new infrastructure in communication for transmitting audio data. This is evidenced by the large number of communication media, both wired and wireless. So that it raises new methods for sending audio data, one of which is using Visible Light Communication (VLC). VLC is a communication system for transmitting and receiving data using the visible light wave spectrum between 375 nm - 780 nm. In this research, audio data communication utilizes the brightness of the LED light. The transmitter and receiver use an LED component as a transducer which is then sent to the data processing circuit. From the data processing circuit then sent to the audio amplifier circuit. From the test results it can be shown that this system can transmit audio data. Based on the LED color test, Green produces the highest output voltage of 1.32 Volt. The angle limit that can be detected by the photo diode is at an angle of 70Â° with a measured voltage of 100mV and the resulting sound intensity of -32.541dB.